Surgical Management with Self-Locking Pins and Circumferential Wiring for Treating Comminuted Patella Fractures Achieved Seiza-Style Sitting - Kizaki, Kazuha; Uchida, Soshi; Funakoshi, Noboru; Mori, Daisuke; Nakai, Ryosuke; Yamashita, Fumiharu (Joints, 2019)
Surgical fixation of comminuted patella fractures is technically challenging. Despite the fact that tension band wiring or screw fixation are the most common surgical procedures, these surgical techniques have crucial limitations for laterally scattered fragments. We demonstrate two cases with comminuted patella fractures undergoing surgical fixation with self-locking pin and circumferential wiring, confirming the rigid fixation achieving deep knee flexion. After midline longitudinal skin incision, 2.0 mm stainless pins (AiMedic MMT, Tokyo, Japan) were inserted radially to penetrate each fragment and 1.2 mm stainless wire was circumferentially looped and self-locked in the holes on the pins, which satisfied rigid fixation. Any restrictions in range of motion and weight bearing were required postoperatively and 3- to 6-month postoperative cares achieved seiza-style sitting with deep knee flexion.
Keywords: patella fracture; comminuted; surgical management